Korean-Canadian Children’s Bilingualism: Language Positions and Supporting Factors Within and Beyond a Multi-Generational Ethnic Church - Jang, Soon Young (Journal of the Canadian Association for Curriculum Studies, 2020)
Adopting Bourdieu’s (1991) theoretical and analytic tools of field, habitus and capital, this year-long ethnographic case study examines the positions of the Korean and English languages at various levels within a multi-generational ethnic church. The research also identifies multiple levels of supporting factors of Korean-Canadian children’s bilingual development within and beyond this church. Data sources include classroom observations, interviews, curriculum materials, children’s artifacts, Korean government documents, as well as records of school meetings. In this study, the positions of Korean and English within the church are unveiled in the Korean and English ministries, which are closely linked to immigrant generations, and in the language use and socialization of children in the Grades 3 and 4 focus class. The positions of the languages within the church are influenced by the status of those languages beyond the church, demonstrating the close relationship between language and identity. This study also finds that the Korean language school in this church is a field in which the aims of the Korean government and Korean-Canadian immigrants intersect vis-à-vis heritage language education. For the Korean government, it is ultimately a field for strengthening national resources. For the church congregants, it is essentially for their heritage language and culture maintenance.